1997
DOI: 10.1128/mcb.17.9.5400
|View full text |Cite
|
Sign up to set email alerts
|

The Orphan Nuclear Receptor Estrogen-Related Receptor α Is a Transcriptional Regulator of the Human Medium-Chain Acyl Coenzyme A Dehydrogenase Gene

Abstract: Estrogen-related receptor ␣ (ERR␣) is an orphan member of the superfamily of nuclear hormone receptors. ERR␣ was initially isolated based on its sequence homology to the estrogen receptor but is not activated by classic estrogens. To identify possible physiologic functions for this orphan receptor, we cloned the mouse ERR␣ cDNA and used it to characterize the expression of ERR␣ transcripts and to identify potential ERR␣ target genes. RNA in situ hybridization studies detect ERR␣ transcripts in an organ-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
335
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(349 citation statements)
references
References 38 publications
13
335
1
Order By: Relevance
“…The lower amount of phospo-labeled ERRa1 observed in the 4D5-treated cells was due to this treatment being inhibitory to cell growth (data not shown). Thus, we confirmed prior reports that ERRa1 is a phosphoprotein (9,38). We also conclude that ERRa1 was phosphorylated in vivo at several sites, with the extent of phosphorylation being cell type dependent and reduced by disruption of the ErbB2 signaling pathway.…”
Section: Extent Of Phosphorylation Of Erra1 Correlates With Its Abilisupporting
confidence: 79%
“…The lower amount of phospo-labeled ERRa1 observed in the 4D5-treated cells was due to this treatment being inhibitory to cell growth (data not shown). Thus, we confirmed prior reports that ERRa1 is a phosphoprotein (9,38). We also conclude that ERRa1 was phosphorylated in vivo at several sites, with the extent of phosphorylation being cell type dependent and reduced by disruption of the ErbB2 signaling pathway.…”
Section: Extent Of Phosphorylation Of Erra1 Correlates With Its Abilisupporting
confidence: 79%
“…We have demonstrated that E 2 induction of ERR␣ relies on the MAPK signaling pathway as it is susceptible to a MAPK inhibitor. Stimulation of the MAPK pathway by estrogen can lead to the activation of ERR␣ via phosphorylation (22,78). Phosphorylated ERR␣ binds DNA and interacts with co-activators more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…7 ESRRA is expressed in several tissues, but most abundantly in tissues with a high capacity for b-oxidation, such as skeletal muscle, heart, kidney, liver and adipose tissue. 1,8 The esrra knockout (KO) mouse has reduced body weight, diminished lipogenesis in adipose cells and exhibits resistance to dietinduced obesity, indicating that ERRa may be a potent regulator of energy metabolism in vivo. 9 Specifically, through interaction with the peroxisome proliferator-activated receptor-g coactivator-1a (PGC-1a) and the peroxisome proliferator-activated receptor a (PPARa), ERRa has been reported to regulate the medium-chain acyl-CoA dehydrogenase (MCAD), an enzyme involved in the oxidation of fatty acids.…”
Section: Introductionmentioning
confidence: 99%